Resiliensi Nelayan Pencari Telur Ikan Terbang Dalam meningkatkan Kesejahteraan Keluarga di Pulau Masalima Kabupaten Pangkep - Wahyuni, Beviana; Mandjarreki, Sakaruddin; Muh. Anwar (Universitas Islam Negeri Alauddin Makassar, 2025)
The main topic of this research is to discuss: 1) How is the resilience strategy of fishermen seeking flying fish eggs to increase their resilience to climate changes and market prices on Masalima Island? 2) What are the challenges faced by fishermen seeking flying fish eggs on Masalima Island? This thesis is a qualitative research method with descriptive analysis and a sociological approach. Data collection techniques used include direct observation, interviews, and documentation on Masalima Island, Liukang Kalmas District, Pangkep Regency. The data analysis techniques applied include the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of this study are not optimal and require improvement. Regarding the resilience strategy of Pattorani or flying fish egg seekers, it provides an overview of the ability of coastal communities to face social, economic, and ecological challenges adaptively and sustainably. However, fishermen face threats of climate/weather changes and sea conditions, barges on the northern and southern routes, engine damage, and broken epe-epe as well as limited access to market prices. In dealing with fluctuations in catches, they rely on adaptive strategies such as income diversification and community cooperation. The implications of this study indicate that Pattorani fishermen or flying fish egg collectors have high adaptive abilities in facing social, economic, and ecological challenges through sustainable traditional practices on Masalima Island.